Atypical Metronidazole-Induced Encephalopathy in Anaerobic Brain Abscess - Jang, Han Jin (The Korean Neurosurgical Society, 2012)
Metronidazole-induced encephalopathy is a very rare complication of the long standing use of metronidazole. The encephalopathy is bilateral and symmetric in nature. We report on the magnetic resonance imaging (MRI) and clinical course of metronidazole-induced encephalopathy in a 60-year-old female with a persistent anaerobic brain abscess after draining of the abscess. After 3 months of metronidazole administration, the patient complained of dysarthria, tingling sense of all extremities, and left hemiparesis. MRI revealed symmetric hyperintensity lesions in medulla, pons, dentate nuclei of cerebellum, and splenium of corpus callosum, all of which represent typical findings of metronidazole-induced encephalopathy. In addition, asymmetric lesions in midbrain, thalamus, putamen and cerebral subcortical white matter were noted. The patient recovered after discontinuation of metronidazole and the remaining abscess was successfully treated with meropenem and levofloxacine.